2008
DOI: 10.4314/njm.v17i3.37396
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Nigeria: A 10-Year Analysis of the Kano Cancer Registry

Abstract: Background: Cancer is a major health problem in developed countries and epidemiological evidence shows the emergence of a similar tend in developing countries, particularly in sub-Saharan Africa where HIV/AIDS is predicted to augment the cancer burden. The present study analyses the profile of cancers recorded in the first decade (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) of establishment of the Kano cancer registry (KCR) a histology/ cytology-based registry in Kano, Nigeria. Methods: Records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 12 publications
5
52
1
Order By: Relevance
“…Commonly occurring cancers in Nigeria include cervical, breast prostrate, skin, and gastric cancers. [43,44] A population-based survey carried out in Ibadan, covering the time period of 1960-1963, found 648 cases of cancer. It was estimated to represent a crude annual incidence of 45 per 100,000 of the population.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly occurring cancers in Nigeria include cervical, breast prostrate, skin, and gastric cancers. [43,44] A population-based survey carried out in Ibadan, covering the time period of 1960-1963, found 648 cases of cancer. It was estimated to represent a crude annual incidence of 45 per 100,000 of the population.…”
Section: Cancermentioning
confidence: 99%
“…Being hospital based, the true population burden could be higher, since not all cases are reported in the hospital. [44] It is projected that by 2020, cancer incidence in Nigerian males will rise to 90.7/100,000 and for females to100.9/100, 000. [45] A report showed that only 10% of diagnosed cancer cases in Nigeria have access to care.…”
Section: Cancermentioning
confidence: 99%
“…Cancer morbidity and mortality data in Nigeria is unavailable as a result of the absence of national cancer registry 3 . However, the evidence in the literature indicates that prostate cancer is the most commonly diagnosed cancer amongst Nigerian men 4,5 . The higher morbidity and mortality in Nigerian men maybe associated with late presentation at the hospital and being diagnosed at a much older age than men in developed countries 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[23] In an another study that analyzed the profile of cancers recorded in the first decade (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) of establishment of the Kano cancer registry (KCR), a histology/cytology-based registry in Kano, Nigeria, BL (31.4%), other lymphoreticular cancers (23.8%) and retinoblastoma (20%) predominated in children of a total of 1990 cancer cases. [24] EBV is associated with 90% of African patients with BL, but this incidence is significantly lower for BL seen in other parts of the world. In addition, high levels of antibodies to EBV are found in all African children with BL, but in only half of normal African children.…”
Section: Nasopharyngeal Carcinomamentioning
confidence: 91%